MENINGKATKAN HASIL BELAJAR DAN DISPOSISI MATEMATIS SISWA MELALUI MODEL PROBLEM BASED LEARNING - Br Ginting, Aliya Monika; Saleh Haji (LPPM Universitas Advent Indonesia, 2024)
The aim of this research is to improve students' mathematical disposition abilities and learning outcomes through the Problem Based Learning (PBL) model in algebra form material in Class VII of SMP Negeri 29 Rejang Lebong. This research is Classroom Action Research (PTK) with 4 stages, namely 1) Planning, 2) Implementation, 2) Observation, and 4) Reflection. Data collection was carried out through tests on learning outcomes of algebra material and student mathematical disposition questionnaires. Data were analyzed using qualitative analysis. The subjects of this research consisted of 24 class VII students of SMP Negeri 29 Rejang Lebong in the odd semester of the 2023/2024 academic year. Research findings show that the use of the Problem Based Learning (PBL) model can improve students' mathematical disposition abilities and mathematics learning outcomes. The increase in mathematics learning outcomes was 42% in the first cycle and in the second cycle it reached 83%. The increase in students' mathematical disposition indicators increased by 73% for self-confidence, 64% for flexibility, 91% for perseverance, 75% for interest and curiosity, and 71% for reflection, all of which were included in the good criteria in the first cycle. In the second cycle, the scores increased to 79% for self-confidence, 70% for flexibility, 95% for persistence, 80% for interest and curiosity, and 76% for reflection, which showed excellent criteria. Keywords: Learning Outcomes, Mathematical Disposition Ability, Problem Based Learning.